AKREDITASI PENYELENGGARA PERJALANAN IBADAH UMROH (PPIU) SEBAGAI BENTUK KEPATUHAN TERHADAP HUKUM POSITIF DAN PERLINDUNGAN KONSUMEN - Pardiansyah, Dedi; Lulus Setiawan, Wawan (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Organizing Umrah and Hajj pilgrimage trips is included in the Regular Business category where all operations must be guided by positive law comprehensively, starting from licensing of the organizers to service standards to the congregation as consumers. The implementation of the Umrah pilgrimage is regulated and supervised by the government, in this case by the Ministry of Religion of the Republic of Indonesia (KEMENAG R.I) by providing accreditation for Umrah pilgrimage organizers (PPIU). However, it is necessary to examine the extent to which PPIU accreditation is a form of positive legal compliance and consumer protection. Based on this phenomenon, the author conducted research with the title "Accreditation of Umrah Travel Organizers (PPIU) as a Form of Compliance with Positive Laws and Consumer Protection". This research uses a qualitative approach with the Normative - Empirical method. Normatively by tracing and examining positive laws relevant to the implementation of the Umrah pilgrimage and empirically by conducting a triangular study of the implementation of accreditation at PT. Cahaya Cordoba Utama as PPIU. PPIU accreditation is proven to be a form of compliance with positive law, because it fulfills all four principles of legal compliance, namely: Indoctrination, Habituation, Utility and Group Identification. Likewise, PPIU accreditation has been proven to be a form of consumer protection, because all elements in assessing standards for organizing Umrah pilgrimages fulfill all the rights contained in article four of Law no. 8 of 1999 concerning Consumer Protection, both preventive rights and repressive rights.